Study on the Quality Properties of Concrete Using Recycled Sand Produced from Wet Gravity Separation System - Lee, Sangsoo; Song, Hayoung (Asian Journal of Chemistry, 2013)
This study evaluated recycled sand's properties before and after going through the wet gravity separation system. The mechanical properties, shrinkage and durability properties of concrete with different replacement ratios of recycled sand, were compared and analyzed. As a result, it was found that the quality and performance of the recycled sand that has gone through the wet gravity separation system were better than those of the recycled sand that has not gone through the system, because of the removal of impurity content and powder content. Looking at the changes in unit-water content for satisfying the fluidity, it was found that the unit-water content of the concrete using the finally produced recycled sand was similar to that of the concrete using natural sand. The concrete using the recycled sand that has gone through the wet gravity separation system compared to the recycled sand that has not gone through the wet gravity separation system, showed superior performance in compressive strength, shrinkage and durability.